2004
DOI: 10.1038/sj.ijo.0802875
|View full text |Cite
|
Sign up to set email alerts
|

Freiburg Intervention Trial for Obese Children (FITOC): results of a clinical observation study

Abstract: BACKGROUND:The Freiburg Intervention Trial for Obese Children (FITOC) is an interdisciplinary, outpatient program for obese children consisting of regular physical exercise and comprehensive dietary and behavioral education. Parental involvement is required. The study is designed as a longitudinal, nonrandomized clinical observation study. An 8-month intensive phase preceded a follow-up phase of 1 y or longer. METHODS: Data were collected from 31 groups comprising 496 children (267 girls, 229 boys), with an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 29 publications
2
48
1
8
Order By: Relevance
“…9,10 The achieved weight loss and its maintenance were more pronounced and most importantly sustained as compared to previous studies. [11][12][13][14] Apart from differences in age, race and degree of overweight, this finding can probably be explained Four-year follow-up after intervention T Reinehr et al in part by proving the motivation at the beginning of the intervention using criteria, which have been reported to be predictive for success. 4 Furthermore, the combination of individual care and group sessions, the intensive education of parents and the graduated structure of the intervention might be factors leading to long-term success.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The achieved weight loss and its maintenance were more pronounced and most importantly sustained as compared to previous studies. [11][12][13][14] Apart from differences in age, race and degree of overweight, this finding can probably be explained Four-year follow-up after intervention T Reinehr et al in part by proving the motivation at the beginning of the intervention using criteria, which have been reported to be predictive for success. 4 Furthermore, the combination of individual care and group sessions, the intensive education of parents and the graduated structure of the intervention might be factors leading to long-term success.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some treatment programmes with large empirical basis have been reported, showing effective long-term results, mainly in children with supportive families (Epstein et al, 1990a, b (bis) ;Epstein, 1996;Braet and Van Winckel, 2000;Golan and Crow, 2004). Moreover, numerous clinic-based trials have indicated that potentially successful interventions for obese children should be multidimensional combining the following strategies: to adopt a health-centred rather than weight-centred lifestyle; to reduce energy intake while maintaining optimal nutrient intake; to increase physical activity and to reduce sedentariness; to actively involve parents in the changing process, mainly in younger children; to facilitate a supportive family environment; to achieve small and gradual changes, using methods and techniques of the cognitive-behavioural therapy (Epstein, 1996;Warschburger et al, 2001;Eliakim et al, 2002;de Mello et al, 2004;Reinehr et al, 2005;Sacher et al, 2005;Korsten-Reck et al, 2005;Nemet et al, 2005;Jiang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The cost of running an intervention study was not mentioned in any of the seven studies in the original meta-analysis. In the current meta-analysis, several of the 16 studies (Croker et al, 2005;Korsten-Reck et al, 2005;Reinehr et al, 2010), all conducted outside the United States, discussed the issue of cost for the intervention programs. Yin et al (2005) also discussed the need for cost-effective intervention programs that could be sustained.…”
Section: Cost Of Interventionsmentioning
confidence: 99%
“…The weight loss interventions also varied from providing a single intervention (n = 5): Dietary (Rosado, Arellano, Montemayor, García, & Caamaño, 2008 [two interventions]), or physical activity (Farpour-Lambert et al, 2009;Lazaar et al, 2007;Maddison et al, 2011). A majority of the studies (n = 14) used a combination of strategies: education and behavior (Wong & Cheng, 2013 (Carrel et al, 2005;Davis, Ventura, Cook, Gyllenhammer, & Gatto, 2011;Harder-Lauridsen et al, 2014); diet and education (Rosado et al, 2008); diet, physical activity, and behavioral changes (Adam, Westenhofer, Rudolphi, & Kraaibeek, 2009;Croker et al, 2012;Janicke et al, 2008;Korsten-Reck, Kromeyer-Hauschild, Wolfarth, Dickhuth, & Berg, 2005;Maddison et al, 2014;Reinehr, 2010;Satcher et al, 2010) (see Table S3, available with online version of this article).…”
Section: Treatment the Type Of Weight Loss Interventions In The 16mentioning
confidence: 99%